Dietary and Exercise Interventions for Perimenopausal Women: A Health Status Impact Study - Hao, Shuping; Tan, Sisi; Li, Jing; Li, Weimin; Li, Jingyun; Cai, Xiaochen; Hong, Zhongxin (Frontiers in Nutrition, 2022)
Purpose To explore the impact of different intervention methods on physical health indexes of perimenopausal women. Methods Seventy-eight perimenopausal women were divided into three groups. Group A received routine gynecological diagnosis and treatment and participated in centralized lifestyle health education. Group B was required to participate in all intensive education content, and professional dietitians gave individualized dietary guidance. Group C received intensive education, individualized diet intervention and intensified resistance exercise. Dietary scores, exercise habits, waist circumference, body mass index, fat and muscle mass were observed after three months. Results After the intervention, the total diet score of group C was higher than groups A and B, and the red meat score was significantly reduced. The number of patients in groups B and C who exercised >3 times per week and the number of resistance exercises were significantly increased, while the number of aerobic exercises per week in group C was significantly increased. The body fat and waist circumference were significantly reduced, and skeletal muscle weight was significantly increased. Body mass index, trunk fat ratio and waist-to-hip ratio were significantly decreased in groups B and C, while trunk muscle was significantly increased in group C. Conclusion The combined intervention of the three methods can give full play to the synergistic effect of various interventions. The improvement effect of increasing the appropriate amount of resistance exercise is more obvious, which is worthy of further promotion and application.